Restorasi Meiji dan Kolaborasi Negara-Masyarakat Dalam Kekuatan Ekonomi Politik Jepang - Kisno Hadi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2025)
This article is a research that using qualitative descriptive method and literature approach. It describes on the rise of economic and political power of Japan since Meiji Restoration. There are four research result i.e,. firstly, Meiji Restoration was an openess era for structure and sistem of state administration of Japan. Confusianism tradition as characteristic of Japan’s culture became the spirit that impact for strenghtening economic and political power of Japan until nowadays. Secondly, the involvement of Zaibatsu (rich family grups) to build economic system by fasilitating these groups to set up multinational companies and paved the way to invest to abroad contries. Thirdly, Japan has confirm the policy that investment of the Zaibatsu company in abroad country is supporting national interest. In other words, domestic investment takes precendence. And the last, the main weakness of Japan is avoidance to make direct competition to US in it’s foreign policies. As the result, disparity of investment between domestic and abroad. This research will analysis by applying political economic power approach of Caporaso.